Resveratrol Modulates Desaturase Expression and Fatty Acid Composition of Cultured Hepatocytes - Kühn, Gianna; Pallauf, Kathrin; Schulz, Carsten; Birringer, Marc; Diaz-Rica, Beatriz; de Pascual-Teresa, Sonia; Rimbach, Gerald (Frontiers in Nutrition, 2018)
This study aimed to evaluate whether resveratrol (RSV) and its microbial metabolites dihydro-resveratrol (DHR) and lunularin (LUN) affected fatty acid metabolism and omega-3 polyunsaturated fatty acid (n3-PUFA) synthesis in cultured hepatocytes. To this end, cultured human HepG2 hepatocytes were treated with non-toxic concentrations of these polyphenols (40µM) and Δ5- and Δ6-desaturase (FADS1 and FADS2, respectively) expression was measured. Resveratrol induced both genes but DHR and LUN showed no effect. Co-incubation of RSV with α-linolenic acid (ALA) also induced FADS1 and FADS2 expression. Moreover, transcription of carnitine palmitoyltransferase 1A and fatty acid synthase expression was increased, indicating induction of β-oxidation and fatty acid synthesis, respectively. Using gas chromatography to measure fatty acid levels, we observed the impact of RSV with and without ALA treatment on fatty acid composition. However, RSV reduced unsaturated while increasing saturated fatty acid levels. We found lower amounts of monounsaturated fatty acids (16:1n-7c, 18:1n-9c, 18:1n7c and 20:1n-9) and n3-PUFA docosahexaenoic acid whereas unsaturated fatty acid levels, especially of stearic acid, were elevated. Of interest, once we co-incubated the cells with RSV together with bovine serum albumin, we found no differences in gene expression compared to cells without RSV treatment. Although we found no positive effect of RSV on n3-PUFA synthesis, the stilbene could possibly prevent cellular stress by decreasing unsaturated fatty acid levels.